1999
DOI: 10.1200/jco.1999.17.10.3333
|View full text |Cite
|
Sign up to set email alerts
|

American Society of Clinical Oncology Clinical Practice Guidelinesfor the Use of Chemotherapy and Radiotherapy Protectants

Abstract: Mesna: (1) Mesna, dosed as detailed in these guidelines, is recommended to decrease the incidence of standard-dose ifosfamide-associated urothelial toxicity. (2) There is insufficient evidence on which to base a guideline for the use of mesna to prevent urothelial toxicity with ifosfamide doses that exceed 2.5 g/m(2)/d. (3) Either mesna or forced saline diuresis is recommended to decrease the incidence of urothelial toxicity associated with high-dose cyclophosphamide use in the stem-cell transplantation settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
142
0
9

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(155 citation statements)
references
References 74 publications
1
142
0
9
Order By: Relevance
“…The American Society Clinical Oncology Guidelines for the use of chemoprotectants does not support the routine use of amifostine [58]. At the time the guidelines were prepared, there were no data from phase II or III studies to evaluate whether amifostine protects against paclitaxel neurotoxicity.…”
Section: Amifostinementioning
confidence: 99%
See 1 more Smart Citation
“…The American Society Clinical Oncology Guidelines for the use of chemoprotectants does not support the routine use of amifostine [58]. At the time the guidelines were prepared, there were no data from phase II or III studies to evaluate whether amifostine protects against paclitaxel neurotoxicity.…”
Section: Amifostinementioning
confidence: 99%
“…The available clinical data were from a phase I doseescalation study of paclitaxel (3-hour infusion) and amifostine. Twenty-two patients with advanced malignancies were treated with 910 mg/m 2 of amifostine and escalating doses of paclitaxel starting at 135 mg/m 2 up to 310 mg/m 2 [58]. Higher doses of paclitaxel were reached when drug administration was preceded by amifostine.…”
Section: Amifostinementioning
confidence: 99%
“…9 Amifostine (WR-2721) is an organic thiophosphate compound which selectively protects normal tissue from the cytotoxic damage induced by anticancer agents. 10 The protective effect of amifostine was first demonstrated in cells exposed to radiation. 11 Interest in the potential value of amifostine in cancer therapeutics further increased when it was recognized in phase II and phase III clinical trials that amifostine also protected normal tissues, but not tumor cells against the toxic effects of several chemotherapeutic agents, [12][13][14][15][16][17][18][19] reducing the occurrence and severity of neutropenia and other non-hematological toxicities without affecting anti-cancer efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Dexrazoxane protects against the cardiotoxicity of anthracyclines, at least in part, through the chelation of intracellular iron, which may decrease anthracyclineinduced free radical generation. 8 Dexrazoxane has also been reported to inhibit the catalytic activity of topoisomerase II and to potentiate the efficacy of a number of antitumor agents. 25,26 Recently, dexrazoxane has shown protection against anthracycline extravasation, but the precise mechanism was not defined.…”
Section: Discussionmentioning
confidence: 99%
“…7 Dexrazoxane is a derivative of EDTA that has been shown to decrease significantly the incidence of cardiomyopathy in patients treated with anthracyclines. 8 Results of a randomized trial demonstrated that dexrazoxane protects against the development of cardiotoxicity when high single doses of epirubicin are used, without affecting antitumor activity. 7 No data are available regarding the use of dexrazoxane in combination with high-dose anthracyclines, with or without other agents, for PBSC mobilization.…”
Section: Discussionmentioning
confidence: 99%